Active Detection of Shielded SNM With 60-keV Neutrons - Hagmann, C.A.; Dietrich, D.D.; Hall, J.M.; Kerr, P.L.; Nakae, L.F.; Newby, R.J.; Rowland, M.S.; Snyderman, N.J.; Stoeffl, W. (IEEE transactions on nuclear science, 2009)
Fissile materials, e.g., 235 U and 239 Pu, can be detected non-invasively by active neutron interrogation. A unique characteristic of fissile material exposed to neutrons is the prompt emission of high-energy (E > 1 MeV) fission neutrons. One promising mode of operation subjects the object to a beam of low-energy (E < 1 MeV) neutrons, generated by a proton beam impinging on a Li target. The emergence of high-energy secondary neutrons then clearly indicates the presence of fissile material. Our interrogation system comprises a low-dose 60-keV neutron generator (5 times 10 6 /s ), and a 1 m 2 array of scintillators for high-energy neutron detection. Preliminary experimental results demonstrate the detectability of small quantities (376 g) of 235 U shielded by steel (200 g/cm 2 ) or plywood (30 g/cm 2 ), with a typical measurement time of 1 min.